[Dr. Simplicio Bisa received the gawad ng pagkilala] - Bisa, Simplicio P. (Animo Repository, 1998)
Dr. Simplicio Bisa of the Philippine Languages Dept. received the Gawad ng Pagkilala during the celebration of Araw ni Balagtas held on April 2. He was cited for his significant contributions to promote Filipino language and literature.